A large genomic island allows Neisseria meningitidis to utilize propionic acid, with implications for colonization of the human nasopharynx. Issue 2 (27th June 2014) - Catenazzi, Maria Chiara E.; Jones, Helen; Wallace, Iain; Clifton, Jacqueline; Chong, James P. J.; Jackson, Matthew A.; Macdonald, Sandy; Edwards, James; Moir, James W. B.
Summary N eisseria meningitidis is an important human pathogen that is capable of killing within hours of infection. Its normal habitat is the nasopharynx of adult humans. Here we identify a genomic island (the prp gene cluster) in N. meningitidis that enables this species to utilize propionic acid as a supplementary carbon source during growth, particularly under nutrient poor growth conditions. The prp gene cluster encodes enzymes for a methylcitrate cycle. Novel aspects of the methylcitrate cycle in N. meningitidis include a propionate kinase which was purified and characterized, and a putative propionate transporter. This genomic island is absent from the close relative of N. meningitidis, the commensal Neisseria lactamica, which chiefly colonizes infants not adults. We reason that the possession of the prp genes provides a metabolic advantage to N. meningitidis in the adult oral cavity, which is rich in propionic acid‐generating bacteria. Data from classical microbiological and sequence‐based microbiome studies provide several lines of supporting evidence that N. meningitidis colonization is correlated with propionic acid generating bacteria, with a strong correlation between prp‐containing Neisseria and propionic acid generating bacteria from the genus Porphyromonas, and that this may explain adolescent/adult colonization by N. meningitidis.